Co-expression of thermophilic pectinases in a single host for cost-effective pectin bioconversion into D-galacturonic acid - Flores-Fernández, Carol N.; Cárdenas-Fernández, Max; Lye, Gary J.; Ward, John M. (Frontiers in Catalysis, 2023)
Co-expression of enzymes allow to produce multiple enzymes in a single host, representing a cost-effective alternative in bioprocesses such as pectin bioconversion. Pectin-rich biomass is an abundant by-product from the fruit and sugar industries that is usually disposed in landfill or sold as a low value feedstock. The aim of this work was to co-express thermophilic pectin methyl esterase (PME) and exo-polygalacturonases (exo-PGs) in a single host for pectin bioconversion into D-galacturonic acid (GalA) using different pectic substrates such as apple, citrus and sugar beet pectin. To achieve this, a PME from Bacillus licheniformis (BLI09) with either an exo-PG from Thermotoga maritima (TMA01) or from Bacillus licheniformis (BLI04) were cloned in pETDuet-1 and co-expressed in E. coli BL21(DE3). Four co-expression constructs were obtained and factors such as the effect of the genes’ cloning order and their expression were evaluated. Co-expression constructs 3 and 4 (pETDuet-TMA01-BLI09 and pETDuet-BLI04-BLI09, respectively) showed good expression of both pectinases compared to co-expression constructs 1 and 2 (pETDuet-BLI09-TMA01 and pETDuet-BLI09-BLI04, respectively). The synergistic activity of the co-expressed pectinases on the three pectic substrates was assayed using the clarified lysates. Co-expression constructs 3 and 4 were the most efficient reaching 3 and 2.5 mM GalA, respectively from apple and citrus pectin after 4 h reaction. In conclusion, this work demonstrates that the co-expression of pectinases can potentially contribute to reduce the cost associated to their production and purification as well as to increase their applicability for exploiting pectin-rich biomass to obtain bio-based chemicals.